2011
DOI: 10.1007/s00421-011-2037-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the performance, energetics and biomechanics of international versus national level swimmers during a competitive season

Abstract: The purpose of this study was to track and compare the changes of performance, energetic and biomechanical profiles of international (Int) and national (Nat) level swimmers during a season. Ten Portuguese male swimmers (four Int and six Nat level subjects) were evaluated on three different time periods (TP(1), TP(2), TP(3)) of the 2009-2010 season. Swimming performance was assessed based on official time's lists of the 200-m freestyle event. An incremental set of 7 × 200 m swims was applied to assess the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…Men have a higher peak leg power compared to women [42][43][44][45][46] mainly due to their higher lean leg volume 42,44,46 . Seifert stability in performances with energetic and biomechanical capacities continuously 49 . Another finding was that the sex difference of national swimmers became greater across the years for 100-m backstroke and all freestyle distances with no changes in international level.…”
Section: Sex Difference In Swimming Performancementioning
confidence: 99%
“…Men have a higher peak leg power compared to women [42][43][44][45][46] mainly due to their higher lean leg volume 42,44,46 . Seifert stability in performances with energetic and biomechanical capacities continuously 49 . Another finding was that the sex difference of national swimmers became greater across the years for 100-m backstroke and all freestyle distances with no changes in international level.…”
Section: Sex Difference In Swimming Performancementioning
confidence: 99%
“…national versus international level) [35]. Additionally, international swimmers are able to maintain a higher energetic and biomechanical capacity than national swimmers [15] and high-speed swimmers have a higher and more stable stroke length and index of coordination than low-speed swimmers [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Little data is known for changes in freestyle swimming performance across years for swimmers competing at national level [11] and no data exist for changes in swimming performance over time for other strokes such as breaststroke [14]. Differences in performance between athletes competing at international and national level are related to differences in the energetic and biomechanical profiles of these athletes [15-18]. Considering breaststroke, Seifert et al [19] reported differences in the elbow-knee continuous relative phase in breaststroke swimmers of different performance levels.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the lower body mass in relation to active mass is conductive to train for speed and endurance, which is typical in short track (Hoffman et al 2009;Nemoto et al 1990). On the other hand, during such a training, the economy of energy reserve usage is being increased which constitute a competitor's protection from a sudden decrease of physical effort ability (Buglione et al 2011;Costa et al 2012;Szymański et al 2010). According to Bomp and Haff (2010) the basic factor determining high effort adaptation during endurance sports like short track, is not training volume, but adequate diversity of trainings and various intensity ranges.…”
Section: Discussionmentioning
confidence: 99%